1984
DOI: 10.2307/2443756
|View full text |Cite
|
Sign up to set email alerts
|

Floral Biology and Breeding System of Bauhinia benthamiana Taub. (Leguminosae), a Bat-Pollinated Tree in Venezuelan "Llanos"

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Botanical Society of America is collaborating with JSTOR to digitize, preserve and extend access to American Journal of Botany.http://www.jstor.org Amer. J. Bot. 71(2): 273-28… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
13
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Wyatt and Shannon (1986) found that Ascfepias exaltata flowers with concentrated nectar received more visits and matured more fruits than flowers with dilute nectar, but unlike these cactus species, nectar concentration decreased with volume. For Buuhinia ungulata, nectar concentration increased with volume, and the times of greatest nectar production and concentration and of most frequent visits by bat pollinators coincided (Ramirez et al 1984). The timing of reward availability within a night has several potential outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Wyatt and Shannon (1986) found that Ascfepias exaltata flowers with concentrated nectar received more visits and matured more fruits than flowers with dilute nectar, but unlike these cactus species, nectar concentration decreased with volume. For Buuhinia ungulata, nectar concentration increased with volume, and the times of greatest nectar production and concentration and of most frequent visits by bat pollinators coincided (Ramirez et al 1984). The timing of reward availability within a night has several potential outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…They eat nectar, fruit, flower parts, pollen, and insects (Rasweiler, 1975, 1977; Alveraz et al, 1991). G. soricina is important ecologically; several night‐blooming plants rely on them for pollination (Ramirez et al, 1984; Silva and Peracchi, 1999; Zortea, 2003).…”
mentioning
confidence: 99%
“…Variations in temporal and spatial abundance of resources, besides determining the pattern of foraging of bat species, may allow the sharing of these resources (Sazima & Sazima 1978, Fleming 1982, Heithaus 1982. Bat pollination has been recorded in various species of Baubinia (Heithaus et al 1974, Bergallo 1990, Hokche & Ramirez 1990, and the pollination and floral biology of Baubinia ungulata L. (Leguminosae, Caesalpinioidea) has been described by Ramirez et al (1984). The present note focuses on the interactions between three species of nectarivorous bats which pollinate B. ungulata during different flowering periods.…”
mentioning
confidence: 99%